2008
DOI: 10.1242/jcs.027334
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Crk and CrkL expression blocks reelin-induced dendritogenesis

Abstract: The reelin signaling pathway regulates nervous system function after birth, in addition to its role in regulating neuronal positioning during embryogenesis. The receptor-dependent, reelin-induced tyrosine phosphorylation of the Dab1 docking protein is an established prerequisite for biological responses to this ligand. Here we show that the inactivation of a conditional Dab1 allele reduces process complexity in correctly positioned neurons in the CA1 region of the mouse hippocampus after birth. Reelin stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 38 publications
8
73
1
1
Order By: Relevance
“…CrkII and CrkL have overlapping functions in dendritogenesis, phagocytosis, and actin reorganization (24,37,42). In this study, we observed that CrkII and CrkL play a similar role in osteoclasts as in other cell types (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…CrkII and CrkL have overlapping functions in dendritogenesis, phagocytosis, and actin reorganization (24,37,42). In this study, we observed that CrkII and CrkL play a similar role in osteoclasts as in other cell types (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Numerous independent studies and observations point toward a role for Reelin and ApoE receptors in the formation of neuronal connections (Del Rio et al 1997;Borrell et al 2007) and the generation of dendritic complexity Costa et al 2001;Niu et al 2004;Matsuki et al 2008;Hoe et al 2009). The latter may, however, not be entirely dependent on Apoer2 and Vldlr (Chameau et al 2009) and may also involve interactions with APP (Hoe et al 2009).…”
Section: Regulation Of Dendritic Spines Glutamatergic Neurotransmissmentioning
confidence: 99%
“…Recently, it has been demonstrated that Reelin participates in the composition, recruitment and traffic of NMDA receptor subunits (Chen et al, 2005;Qiu et al, 2006;Groc et al, 2007), in the generation of dendrites, and in the formation of dendritic spines (Matsuki et al, 2008;Niu et al, 2008). Furthermore, the lack of spines in cultured reeler neurons is recovered by incubation with Reelin (Matsuki et al, 2008;Niu et al, 2008). Altogether, these studies suggest that Reelin is involved in the correct formation and maintenance of synapses.…”
Section: Introductionmentioning
confidence: 95%
“…Although the role of Reelin in the adult brain is not well understood, it has been shown that this protein is expressed in synaptic contacts, and that neurons deficient in ApoER2 and VLDLR receptors have impaired long-term potentiation (LTP) Beffert et al, 2005). Recently, it has been demonstrated that Reelin participates in the composition, recruitment and traffic of NMDA receptor subunits (Chen et al, 2005;Qiu et al, 2006;Groc et al, 2007), in the generation of dendrites, and in the formation of dendritic spines (Matsuki et al, 2008;Niu et al, 2008). Furthermore, the lack of spines in cultured reeler neurons is recovered by incubation with Reelin (Matsuki et al, 2008;Niu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%